Positive electrode material for electric devices and all-solid-state lithium secondary battery using the same

The positive electrode material with a specific Raman spectrum and electrolyte interaction enhances the capacity and durability of all-solid lithium secondary batteries by maintaining a high number of reaction points, addressing discharge capacity and cycle durability issues.

JP7615762B2Active Publication Date: 2025-01-17NISSAN MOTOR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021030334
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-26
Publication Date
2025-01-17
Estimated Expiration
2041-02-26

AI Technical Summary

Technical Problem

Existing all-solid-state lithium secondary batteries using sulfur as a positive electrode active material face challenges in achieving sufficient discharge capacity and maintaining capacity over repeated charging and discharging cycles, known as cycle durability.

Method used

A positive electrode material is developed where at least a portion of the solid electrolyte and positive electrode active material are in contact, characterized by a specific Raman spectrum with a peak intensity ratio R(I1/I0) ≥ 0.05, enhancing the interaction between sulfur and the solid electrolyte.

Benefits of technology

This configuration improves the capacity characteristics and cycle durability of all-solid lithium secondary batteries by maintaining a high number of reaction points, even with repeated charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615762000002
    Figure 0007615762000002
  • Figure 0007615762000003
    Figure 0007615762000003
  • Figure 0007615762000004
    Figure 0007615762000004
Patent Text Reader

Abstract

To provide means for enhancing the capacity characteristic and cycle durability as to an electric device arranged by use of a sulfur-containing positive electrode active material.SOLUTION: A positive electrode material for an electric device comprises: a conductive material; a solid electrolyte containing a phosphorus sulfide (PxSy); and a sulfur-containing positive electrode active material. In the positive electrode material, at least a part of the solid electrolyte and at least a part of the positive electrode active material are disposed on the surface of the conductive material so as to be in contact with each other. In Raman spectra according to microscopic Raman spectroscopy with a laser of 532 nm in wavelength, the solid electrolyte included in the positive electrode material shows a peak A originating from PS43- near 420 cm-1, and shows peaks B in a range of 1300-1700 cm-1. When I0 is defined as a peak intensity of the peak A, and I1 is defined as a peak intensity of a peak of the peaks B, having the largest peak intensity, the peak intensity ratio R (I1 / I0) satisfies R≥0.05.SELECTED DRAWING: Figure 5A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode material for an electric device and an all-solid-state lithium secondary battery using the same. [Background technology]

[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to combat global warming. In the automobile industry, there are high hopes for a reduction in carbon dioxide emissions through the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and there has been active development of non-aqueous electrolyte secondary batteries, such as motor drive secondary batteries, which hold the key to putting these into practical use.

[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium secondary batteries, which have the highest theoretical energy of all practical batteries, have attracted attention and are currently being rapidly developed.

[0004] Currently, lithium secondary batteries in widespread use use flammable organic electrolytes as electrolytes, and these liquid-based lithium secondary batteries require stricter safety measures against leakage, short circuits, overcharging, etc. than other batteries.

[0005] In recent years, research and development of all-solid-state lithium secondary batteries using oxide-based or sulfide-based solid electrolytes has been actively conducted. A solid electrolyte is a material mainly composed of an ion conductor capable of ion conduction in a solid state. Therefore, in principle, all-solid-state lithium secondary batteries do not have various problems caused by flammable organic electrolytes, as in conventional liquid-based lithium secondary batteries. In addition, the use of high-potential, large-capacity positive electrode materials and large-capacity negative electrode materials generally leads to a significant improvement in the output density and energy density of the battery. For example, elemental sulfur (S8) has an extremely large theoretical capacity of about 1670 mAh / g, and has the advantages of being low cost and abundant in resources.

[0006] On the other hand, metallic lithium, which is a negative electrode active material that supplies lithium ions to a positive electrode, is known as a high-capacity negative electrode material that can be used in all-solid-state batteries. However, in all-solid-state batteries that use metallic lithium as the negative electrode active material and a sulfide solid electrolyte as the solid electrolyte, the metallic lithium and the sulfide solid electrolyte may react with each other, resulting in a deterioration in battery characteristics.

[0007] In order to address such problems, Patent Document 1 proposes a technique of using a composite material containing a conductive agent and an alkali metal sulfide integrated on the surface of the conductive agent as a positive electrode material for an all-solid-state battery. Patent Document 1 claims that by using a positive electrode material having such a configuration, a positive electrode material and a lithium-ion battery are provided that have a high theoretical capacity and can use a negative electrode active material that does not supply lithium ions to the positive electrode. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2012 / 102037 Brochure Summary of the Invention [Problem to be solved by the invention]

[0009] However, as shown in Table 1 of Patent Document 1, even when the above technology is adopted, the discharge capacity that can be extracted is not necessarily sufficient, and there is a problem that the sulfur active material with a large theoretical capacity is not fully utilized. In addition, depending on the application of the secondary battery, it is not sufficient to only have a large extractable capacity, and it is also required to be able to sufficiently suppress the decrease in the extractable capacity even when the battery is repeatedly charged and discharged (i.e., to have sufficient so-called cycle durability).

[0010] Therefore, an object of the present invention is to provide a means for improving the capacity characteristics and cycle durability of an electric device using a positive electrode active material containing sulfur. [Means for solving the problem]

[0011] The present inventors have conducted extensive research to solve the above problems. As a result, they have discovered a method for producing a conductive material and a phosphorus sulfide (P x S y The inventors have found that, in a positive electrode material for an electric device comprising a solid electrolyte containing a sulfur-containing cathode active material, the above-mentioned problems can be solved by arranging at least a portion of the solid electrolyte and at least a portion of the cathode active material on a surface of the conductive material so as to be in contact with each other, and by using a solid electrolyte that exhibits a predetermined Raman spectrum as the solid electrolyte contained in the positive electrode material, and have thus completed the present invention.

[0012] One aspect of the present invention is a method for manufacturing a conductive material comprising: x S y The present invention relates to a positive electrode material for an electric device, comprising a solid electrolyte containing sulfur and a positive electrode active material containing sulfur. The positive electrode material is characterized in that at least a part of the solid electrolyte and at least a part of the positive electrode active material are disposed on the surface of the conductive material so as to be in contact with each other. In addition, the solid electrolyte contained in the positive electrode material is subjected to microscopic Raman spectroscopy using a laser with a wavelength of 532 nm, and a Raman spectrum of 420 cm -1 Nearby PS4 3- and a peak A derived from 1300 to 1700 cm -1 The present invention is also characterized in that when peak B is shown in the range of I0, the peak intensity of peak A is I0, and the peak intensity of the peak B with the greatest peak intensity is I1, the peak intensity ratio R (I1 / I0) satisfies R≧0.05. Effect of the Invention

[0013] According to the present invention, in an electric device using a positive electrode active material containing sulfur, it is possible to improve the capacity characteristics and cycle durability. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a perspective view showing the appearance of a flat laminate-type all-solid-state lithium secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. [Figure 3A] FIG. 3A is a cross-sectional schematic diagram of a positive electrode material in the prior art. [Figure 3B] FIG. 3B is a cross-sectional schematic diagram of a positive electrode material according to one embodiment of the present invention. [Figure 4A] FIG. 4A is an image of powder particles of the sulfur-containing positive electrode material obtained in Example 1 described later, observed with a scanning electron microscope (SEM). [Figure 4B] FIG. 4B is an element map of phosphorus (P) in an observation image of a cross section of a conductive material of powder particles of a sulfur-containing positive electrode material obtained in Example 1 described later, taken by TEM-EDX. [Figure 5A] FIG. 5A is a Raman spectrum obtained by performing microscopic Raman spectroscopy on the solid electrolyte contained in the powder particles of the sulfur-containing positive electrode material obtained in Example 1 described below. [Figure 5B] FIG. 5B is a Raman spectrum obtained by performing microscopic Raman spectroscopy measurement on the solid electrolyte contained in the powder particles of the sulfur-containing positive electrode material obtained in Comparative Example 1 described later. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the description of the claims, and is not limited to only the following embodiment. The dimensional ratios in the drawings are exaggerated for convenience of explanation and may differ from the actual ratios. Hereinafter, the present invention will be described by taking as an example a stacked type (internal parallel connection type) all-solid-state lithium secondary battery, which is one form of secondary battery. As described above, the solid electrolyte constituting the all-solid-state lithium secondary battery is a material mainly composed of an ion conductor capable of ion conduction in a solid. For this reason, the all-solid-state lithium secondary battery has the advantage that, in principle, various problems caused by a flammable organic electrolyte do not occur as in the conventional liquid-based lithium secondary battery. In addition, in general, there is also the advantage that the output density and energy density of the battery can be significantly improved by using a high-potential, large-capacity positive electrode material and a large-capacity negative electrode material.

[0016] One aspect of the present invention is a method for manufacturing a conductive material comprising: x S y and a positive electrode active material containing sulfur, wherein at least a portion of the solid electrolyte and at least a portion of the positive electrode active material are disposed on a surface of the conductive material so as to be in contact with each other, and wherein the solid electrolyte contained in the positive electrode material has a Raman spectrum of 420 cm in a microscopic Raman spectroscopy measurement using a laser having a wavelength of 532 nm. -1 Nearby PS4 3- and a peak A derived from 1300 to 1700 cm -1 and wherein, when the peak intensity of the peak A is I0 and the peak intensity of the peak B having the greatest intensity is I1, the peak intensity ratio R (I1 / I0) satisfies R≧0.05. The electric device positive electrode material according to this embodiment can improve the capacity characteristics and cycle durability of an electric device such as an all-solid-state lithium secondary battery, despite the use of a positive electrode active material containing sulfur.

[0017] FIG. 1 is a perspective view showing the appearance of a flat laminated type all-solid-state lithium secondary battery according to one embodiment of the present invention. FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. 1. The laminated type allows the battery to be compact and have a high capacity. In this specification, the flat laminated type non-bipolar lithium secondary battery (hereinafter also simply referred to as a "laminated type battery") shown in FIG. 1 and FIG. 2 will be described in detail as an example. However, in terms of the internal electrical connection form (electrode structure) of the lithium secondary battery according to this embodiment, it can be applied to both non-bipolar type (internal parallel connection type) batteries and bipolar type (internal series connection type) batteries.

[0018] 1, the stacked battery 10a has a flat rectangular shape, with a negative electrode current collector 25 and a positive electrode current collector 27 for extracting electric power extending from both sides. The power generating element 21 is wrapped in a battery exterior material (laminate film 29) of the stacked battery 10a, and the periphery is heat-sealed, with the power generating element 21 being sealed with the negative electrode current collector 25 and the positive electrode current collector 27 extending to the outside.

[0019] The lithium secondary battery according to the present embodiment is not limited to a laminated flat shape. A wound lithium secondary battery may be cylindrical, or may be a rectangular flat shape obtained by deforming such a cylindrical shape, and is not particularly limited. The cylindrical shape may be a laminate film or a conventional cylindrical can (metal can) as an exterior material, and is not particularly limited. Preferably, the power generating element is housed inside a laminate film containing aluminum. This form can achieve weight reduction.

[0020] There is also no particular limitation on the removal of the current collectors (25, 27) shown in Fig. 1. The negative current collector 25 and the positive current collector 27 may be pulled out from the same side, or the negative current collector 25 and the positive current collector 27 may each be divided into a plurality of pieces and removed from each side, and are not limited to what is shown in Fig. 1. In addition, in a wound type lithium secondary battery, the terminals may be formed using, for example, a cylindrical can (metal can) instead of a tab.

[0021] 2, the stacked battery 10a of this embodiment has a structure in which a flat, generally rectangular power generating element 21, where charge and discharge reactions actually proceed, is sealed inside a laminate film 29, which is a battery exterior material. Here, the power generating element 21 has a structure in which a positive electrode, a solid electrolyte layer 17, and a negative electrode are laminated. The positive electrode has a structure in which positive electrode active material layers 15 containing a positive electrode active material are disposed on both sides of a positive electrode collector 11". The negative electrode has a structure in which negative electrode active material layers 13 containing a negative electrode active material are disposed on both sides of a negative electrode collector 11'. Specifically, the positive electrode, solid electrolyte layer, and negative electrode are stacked in this order such that one positive electrode active material layer 15 and an adjacent negative electrode active material layer 13 face each other with a solid electrolyte layer 17 interposed therebetween. As a result, the adjacent positive electrode, solid electrolyte layer, and negative electrode constitute one unit cell layer 19. Therefore, it can be said that the stacked battery 10a shown in FIG. 1 has a structure in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel.

[0022] As shown in FIG. 2, the outermost positive electrode current collectors located on both outermost layers of the power generating element 21 each have a positive electrode active material layer 15 disposed on only one side, but active material layers may be provided on both sides. In other words, instead of using a current collector exclusively for the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as it is as the outermost layer current collector. In some cases, the negative electrode active material layer 13 and the positive electrode active material layer 15 may be used as the negative electrode and positive electrode, respectively, without using the current collectors (11', 11")

[0023] Negative current collector 11′ and positive current collector 11″ are respectively attached with negative current collector plate (tab) 25 and positive current collector plate (tab) 27 that are electrically connected to the respective electrodes (positive and negative electrodes), and have a structure in which they are sandwiched between ends of laminate film 29, which is a battery exterior material, and are led out of laminate film 29. Positive current collector 27 and negative current collector 25 may be attached to positive current collector 11″ and negative current collector 11′ of each electrode by ultrasonic welding, resistance welding, or the like, respectively, via positive electrode leads and negative electrode leads (not shown) as necessary.

[0024] The main components of the lithium secondary battery according to this embodiment will be described below.

[0025] [Current collector] The current collector has a function of mediating the movement of electrons from the electrode active material layer. There are no particular limitations on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.

[0026] The current collector may have a single layer structure made of a single material, or may have a laminate structure in which layers made of these materials are appropriately combined. From the viewpoint of reducing the weight of the current collector, it is preferable to include at least a conductive resin layer made of a resin having conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector. Furthermore, if the negative electrode active material layer and the positive electrode active material layer described later are conductive by themselves and can perform a current collecting function, it is not necessary to use a current collector as a member separate from these electrode active material layers. In such a form, the negative electrode active material layer described later constitutes the negative electrode as it is, and the positive electrode active material layer described later constitutes the positive electrode as it is.

[0027] [Negative electrode (negative electrode active material layer)] In the stacked battery according to the embodiment shown in Fig. 1 and Fig. 2, the negative electrode active material layer 13 contains a negative electrode active material. The type of the negative electrode active material is not particularly limited, but may include a carbon material, a metal oxide, and a metal active material. Examples of the carbon material include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon. Examples of the metal oxide include Nb2O5, Li4Ti5O 12 and the like. Furthermore, silicon-based negative electrode active materials and tin-based negative electrode active materials may be used. Here, silicon and tin belong to the 14th group of elements, and are known to be negative electrode active materials that can greatly improve the capacity of non-aqueous electrolyte secondary batteries. These simple substances can absorb and release a large number of charge carriers (lithium ions, etc.) per unit volume (mass), and therefore become high-capacity negative electrode active materials. Here, it is preferable to use Si simple substance as the silicon-based negative electrode active material. Similarly, SiO 2 disproportionated into two phases, a Si phase and a silicon oxide phase, is also used. x It is also preferable to use silicon oxides such as (0.3≦x≦1.6). In this case, the range of x is more preferably 0.5≦x≦1.5, and even more preferably 0.7≦x≦1.2. Furthermore, an alloy containing silicon (silicon-containing alloy-based negative electrode active material) may be used. On the other hand, examples of negative electrode active materials containing tin element (tin-based negative electrode active materials) include simple Sn, tin alloys (Cu-Sn alloys, Co-Sn alloys), amorphous tin oxides, tin silicon oxides, and the like. Among these, examples of amorphous tin oxides include SnB 0.4 P 0.6 O 3.1Examples of the tin silicon oxide include SnSiO3. When a material not containing lithium (for example, elemental sulfur or lithium sulfide) is used as the positive electrode active material, a metal containing lithium may be used as the negative electrode active material. Such a negative electrode active material is not particularly limited as long as it is an active material containing lithium, and examples thereof include metallic lithium and lithium-containing alloys. Examples of the lithium-containing alloy include alloys of Li and at least one of In, Al, Si and Sn. In some cases, two or more types of negative electrode active materials may be used in combination. Of course, negative electrode active materials other than the above may be used. The negative electrode active material preferably contains metallic lithium, a silicon-based negative electrode active material or a tin-based negative electrode active material, and particularly preferably contains metallic lithium.

[0028] The shape of the negative electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc. When the negative electrode active material is particulate, its average particle diameter (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50 The value of can be measured by a laser diffraction scattering method.

[0029] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is, for example, preferably in the range of 40 to 99 mass %, and more preferably in the range of 50 to 90 mass %.

[0030] The negative electrode active material layer preferably further includes a solid electrolyte. By including the solid electrolyte in the negative electrode active material layer, the ionic conductivity of the negative electrode active material layer can be improved. Examples of the solid electrolyte include sulfide solid electrolytes and oxide solid electrolytes, and the sulfide solid electrolyte is preferable.

[0031] Examples of sulfide solid electrolytes include LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS4, Li3PS4, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In). The description "Li2S-P2S5" means a sulfide solid electrolyte obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.

[0032] The sulfide solid electrolyte may have, for example, a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of sulfide solid electrolytes having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS4, and Li3PS4. Examples of sulfide solid electrolytes having a Li4P2S7 skeleton include Li-PS solid electrolytes called LPS (for example, Li7P3S 11 ) As the sulfide solid electrolyte, for example, Li (4-x) Ge (1-x) P xAn LGPS or the like represented by S4 (where 0 < x < 1) may be used. Among them, a sulfide solid electrolyte containing a P element is preferable, and the sulfide solid electrolyte is more preferably a material mainly composed of Li2S - P2S5. Further, the sulfide solid electrolyte may contain a halogen (F, Cl, Br, I). In a preferred embodiment, the sulfide solid electrolyte contains Li6PS5X (where X is Cl, Br or I, preferably Cl).

[0033] When the sulfide solid electrolyte is a Li2S - P2S5 system, the ratio of Li2S and P2S5 is preferably in the range of Li2S:P2S5 = 50:50 to 90:10 in terms of molar ratio, and more preferably Li2S:P2S5 = 70:30 to 80:20.

[0034] Also, the sulfide solid electrolyte may be a sulfide glass, a crystallized sulfide glass, or a crystalline material obtained by a solid-phase method. The sulfide glass can be obtained, for example, by performing mechanical milling (such as a ball mill) on a raw material composition. Also, the crystallized sulfide glass can be obtained, for example, by performing heat treatment on the sulfide glass at a temperature above the crystallization temperature. The ionic conductivity (for example, Li ion conductivity) of the sulfide solid electrolyte at room temperature (25 °C) is, for example, -5 preferably 1 × 10 -4 S / cm or more, and more preferably 1 × 10 S / cm or more. The value of the ionic conductivity of the solid electrolyte can be measured by an alternating current impedance method.

[0035] Examples of the oxide solid electrolyte include compounds having a NASICON-type structure. As an example of a compound having a NASICON-type structure, a compound represented by the general formula Li 1+x Al x Ge 2-x (PO4)3 (0 ≤ x ≤ 2) (LAGP), a compound represented by the general formula Li 1+x Al x Ti 2-x(PO4)3 (0≦x≦2) (LATP) and the like. Another example of an oxide solid electrolyte is LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.

[0036] The shape of the solid electrolyte may be, for example, a particulate shape such as a spherical shape or an oval spherical shape, or a thin film shape. When the solid electrolyte is particulate, its average particle diameter (D 50 ) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. 50 ) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.

[0037] The content of the solid electrolyte in the negative electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, and more preferably in the range of 10 to 50 mass %.

[0038] The negative electrode active material layer may further contain at least one of a conductive assistant and a binder, in addition to the above-mentioned negative electrode active material and solid electrolyte.

[0039] The thickness of the negative electrode active material layer differs depending on the intended configuration of the secondary battery, but is preferably within the range of, for example, 0.1 to 1000 μm.

[0040] [Solid electrolyte layer] In the stacked battery according to the embodiment shown in FIGS. 1 and 2, the solid electrolyte layer is interposed between the above-mentioned positive electrode active material layer and negative electrode active material layer, and is a layer that essentially contains a solid electrolyte.

[0041] The specific form of the solid electrolyte contained in the solid electrolyte layer is not particularly limited, and the solid electrolytes exemplified in the section on the negative electrode active material layer and their preferred forms can be similarly adopted. In some cases, a solid electrolyte other than the above-mentioned solid electrolytes may be used in combination.

[0042] The solid electrolyte layer may further contain a binder in addition to the above-mentioned predetermined solid electrolyte.

[0043] The thickness of the solid electrolyte layer varies depending on the configuration of the intended lithium secondary battery, but from the viewpoint of improving the volumetric energy density of the battery, it is preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less. On the other hand, there is no particular restriction on the lower limit of the thickness of the solid electrolyte layer, but it is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more.

[0044] [Cathode active material layer] In the stacked battery according to the embodiment shown in FIG. 1 and FIG. 2, the positive electrode active material layer contains a positive electrode material for an electric device according to one embodiment of the present invention. The positive electrode material for an electric device is a conductive material and phosphorus sulfide (P x S y ) and a positive electrode active material containing sulfur.

[0045] (Positive electrode active material containing sulfur) The type of the positive electrode active material containing sulfur is not particularly limited, but may include elemental sulfur (S) and lithium sulfide (Li2S), as well as particles or thin films of organic or inorganic sulfur compounds. Any material may be used as long as it can release lithium ions during charging and absorb lithium ions during discharging by utilizing the oxidation-reduction reaction of sulfur. Examples of the organic sulfur compound include disulfide compounds, sulfur-modified polyacrylonitrile, sulfur-modified polyisoprene, rubeanic acid (dithiooxamide), polycarbonate sulfide, and the like, as typified by the compounds described in the pamphlet of International Publication No. 2010 / 044437. Among these, disulfide compounds, sulfur-modified polyacrylonitrile, and rubeanic acid are preferred, and sulfur-modified polyacrylonitrile is particularly preferred. As the disulfide compound, a dithiobiurea derivative, a compound having a thiourea group, a thioisocyanate, or a thioamide group is more preferred. Here, the sulfur-modified polyacrylonitrile is a modified polyacrylonitrile containing sulfur atoms, which is obtained by mixing sulfur powder with polyacrylonitrile and heating the mixture under an inert gas or under reduced pressure. Its estimated structure is, for example, as shown in Chem. Mater. 2011, 23, 5024-5028, in which polyacrylonitrile is ring-closed to form a polycyclic ring, and at least a part of S is bonded to C. The compound described in this document has a peak at 1330 cm in the Raman spectrum. -1 and 1560cm -1 There is a strong peak signal near 307 cm -1 , 379cm -1 , 472cm -1 , 929cm -1A peak is present around 1000 nm. On the other hand, inorganic sulfur compounds are preferred because of their excellent stability, and specific examples thereof include elemental sulfur (S), Li2S, S-carbon composite, TiS2, TiS3, TiS4, NiS, NiS2, CuS, FeS2, Li2S, MoS2, MoS3, MnS, MnS2, CoS, CoS2, and the like. Among them, elemental sulfur (S), Li2S, S-carbon composite, TiS2, TiS3, TiS4, FeS2, and MoS2 are preferred, elemental sulfur (S), Li2S, TiS2, and FeS2 are more preferred, and elemental sulfur (S) or Li2S is particularly preferred from the viewpoint of high capacity. As elemental sulfur (S), α-sulfur, β-sulfur, or γ-sulfur having an S8 structure can be used.

[0046] The positive electrode material according to the present embodiment may further include a positive electrode active material that does not contain sulfur in addition to the positive electrode active material that contains sulfur. Examples of the positive electrode active material that does not contain sulfur include layered rock salt type active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2, and Li(Ni-Mn-Co)O2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of oxide active materials other than those mentioned above include spinel-type active materials such as LiFePO4 and LiMnPO4, olivine-type active materials such as Li2FeSiO4 and Li2MnSiO4, and Si-containing active materials such as Li4Ti5O 12 Examples include:

[0047] In some cases, two or more kinds of positive electrode active materials may be used in combination. Of course, other positive electrode active materials than those mentioned above may be used. However, the content ratio of the positive electrode active material containing sulfur in the total amount of the positive electrode active material (100% by mass) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass.

[0048] (solid electrolyte) The positive electrode material according to the present invention is phosphorus sulfide (P x S y) includes a solid electrolyte as an essential component. Regarding the specific form of the solid electrolyte contained in the positive electrode material according to this embodiment, there is no particular limitation as long as it contains phosphorus sulfide (P x S y ). Further, in another preferred embodiment, the solid electrolyte contained in the solid electrolyte layer contains an alkali metal atom. Here, examples of the alkali metal that can be contained in the solid electrolyte include Li, Na, or K, and among them, Li is preferable in terms of excellent ionic conductivity.

[0049] Among the above-mentioned solid electrolytes, examples of the solid electrolyte containing phosphorus sulfide (P x S y ) and lithium include, for example, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS4, Li3PS4, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, Li2S-P2S5-Z m S n (m and n are positive numbers, and Z is any one of Ge, Zn, and Ga), LGPS (Li (4-x) Ge (1-x) P x S4 (x satisfies 0 < x < 1)), Li6PS5X (X is Cl, Br, or I, preferably Cl), and the like. Since these solid electrolytes have high ionic conductivity, they can also effectively contribute to the excellent cycle durability and charge-discharge rate characteristics of the electric device.

[0050] In addition, in the positive electrode material according to the present embodiment, the solid electrolyte contained in the positive electrode material is characterized in that it shows a predetermined profile in the Raman spectrum of microscopic Raman spectroscopy using a laser with a wavelength of 532 nm. Here, the Raman spectrum is a spectrum used to grasp the state of a solid, a powder, etc. (for example, Japanese Patent No. 3893816, Japanese Patent No. 3893816, Japanese Patent No. 3929303, Japanese Patent No. 3979352, Japanese Patent No. 4068225, etc.). This Raman spectrum is obtained by Raman spectroscopy, which is suitable for analyzing the surface state of a solid, and can obtain detailed structural information near the solid surface. In addition, the microscopic Raman spectroscopy is Raman spectroscopy performed under a microscope, which makes it possible to analyze the state of a single particle or crystal of a solid.

[0051] Specifically, the solid electrolyte contained in the positive electrode material according to the present embodiment has a Raman spectrum of 420 cm in the microscopic Raman spectroscopy measurement using a laser with a wavelength of 532 nm as described above. -1 Nearby PS4 3- and a peak A derived from 1300 to 1700 cm -1 In this case, peak A is, for example, phosphorus sulfide (P x S y ) derived from PS4 3- The peak corresponds to the ion. On the other hand, the structure corresponding to peak B is not completely clear, but the present inventors have determined that it corresponds to phosphorus sulfide (P x S y ) derived from the oxygen-containing phosphorus sulfide anion (PS x O y n-) is assumed to correspond to the presence of. The solid electrolyte contained in the positive electrode material according to the present embodiment has a characteristic that, in the Raman spectrum, when the peak intensity of the peak A is I0 and the peak intensity of the peak with the highest peak intensity among the peaks B is I1, the peak intensity ratio R (I1 / I0) between them satisfies R≧0.05. The present inventors have found that the positive electrode material according to the present embodiment having such a configuration can improve the capacity characteristics and cycle durability in an electric device such as an all-solid-state lithium secondary battery using a positive electrode active material containing sulfur. From the viewpoint of further improving the capacity characteristics and cycle durability, the value of R preferably satisfies R≧0.10, and more preferably satisfies R≧0.12. The above-mentioned microscopic Raman spectroscopy measurement is not performed on the solid electrolyte in the state of the raw material of the positive electrode material, but is performed on the solid electrolyte after completion as a positive electrode material. Here, the detailed method of the microscopic Raman spectroscopy measurement is adopted as described in the Examples section below.

[0052] (Conductive materials) The positive electrode material according to this embodiment essentially contains a conductive material. There is no particular restriction on the specific form of the conductive material contained in the positive electrode material according to this embodiment, and conventionally known materials can be appropriately adopted. From the viewpoint of excellent conductivity, ease of processing, and ease of designing a desired pore distribution, the conductive material is preferably a carbon material. In particular, the conductive material is more preferably a (porous) carbon material having pores in that it can form more reaction regions (three-phase interfaces), but the conductive material may of course be a carbon material without pores, or may be a conductive material other than a carbon material.

[0053] Examples of carbon materials having pores include carbon particles (carbon carriers) such as activated carbon, Ketjen black (registered trademark; highly conductive carbon black), (oil) furnace black, channel black, acetylene black, thermal black, lamp black, etc., coke, natural graphite, artificial graphite, and the like. On the other hand, examples of carbon materials having no pores include graphene, carbon nanotubes, carbon nanofibers, carbon nanohorns, fullerenes, and the like. Note that the carbon material preferably has carbon as its main component. Here, "having carbon as the main component" means containing carbon atoms as the main component, and includes both the concept of consisting only of carbon atoms and substantially consisting of carbon atoms. "Substantially consisting of carbon atoms" means that the inclusion of impurities of about 2 to 3 mass% or less is allowable.

[0054] The BET specific surface area of the conductive material (preferably a carbon material) having pores is preferably 200 m 2 / g or more, more preferably 500 m 2 / g or more, still more preferably 800 m 2 / g or more, particularly preferably 1200 m 2 / g or more, and most preferably 1500 m 2 / g or more. Further, the pore volume of the conductive material (preferably a carbon material) having pores is preferably 1.0 mL / g or more, more preferably 1.3 mL / g or more, and still more preferably 1.5 mL / g or more. If the BET specific surface area and pore volume of the conductive material are within such ranges, a sufficient amount of pores can be retained, and thus a sufficient amount of the positive electrode active material can be retained. Note that the values of the BET specific surface area and pore volume of the conductive material can be measured by nitrogen adsorption / desorption measurement. This nitrogen adsorption / desorption measurement is performed using BELSORP mini manufactured by MicrotracBEL Corporation at a temperature of -196°C by the multi-point method. The BET specific surface area is determined from the adsorption isotherm in the relative pressure range of 0.01 < P / P0 < 0.05. The pore volume is determined from the volume of adsorbed N2 at a relative pressure of 0.96.

[0055] The average pore diameter of the conductive material is not particularly limited, but is preferably 50 nm or less, and particularly preferably 30 nm or less. If the average pore diameter of the conductive material is within these ranges, electrons can be sufficiently supplied to the active material located away from the pore wall among the positive electrode active materials containing sulfur arranged inside the pores. The average pore diameter of the conductive material can be calculated by nitrogen adsorption / desorption measurement in the same manner as in the case of determining the BET specific surface area and pore volume.

[0056] When the conductive material is particulate, the average particle size (primary particle size) is not particularly limited, but is preferably 0.05 to 50 μm, more preferably 0.1 to 20 μm, and even more preferably 0.5 to 10 μm. In this specification, the "particle size of the conductive material" refers to the maximum distance L between any two points on the contour line of the conductive assistant. The value of the "average particle size of the conductive material" is calculated as the average value of particle sizes of particles observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0057] As described above, the positive electrode material according to the present embodiment is a conductive material and phosphorus sulfide (P x S y ) and a positive electrode active material containing sulfur, and is characterized in that at least a portion of the solid electrolyte and at least a portion of the positive electrode active material are disposed on a surface of the conductive material so as to be in contact with each other.

[0058] FIG. 3A is a schematic cross-sectional view of a cathode material 100' in the prior art. FIG. 3B is a schematic cross-sectional view of a cathode material 100 according to one embodiment of the present invention. In FIG. 3A and FIG. 3B, a carbon material (e.g., activated carbon) 110, which is a conductive material, has a large number of pores 110a. The inside of the pores 110a is filled with sulfur 120, which is a cathode active material. The cathode active material (sulfur) 120 is also disposed on the surface of the carbon material (activated carbon) 110. Here, in the cathode material 100' according to the prior art shown in FIG. 3A, a solid electrolyte (e.g., Li6PS5Cl, which is a sulfide solid electrolyte) 130 is disposed only on the surface of the carbon material (activated carbon) 110. In contrast, in the cathode material 100 according to one embodiment of the present invention shown in FIG. 3B, the solid electrolyte (for example, Li6PS5Cl, which is a sulfide solid electrolyte) 130 is present in a highly dispersed state in the cathode active material (sulfur) 120 disposed on the surface of the carbon material (activated carbon) 110 and on the inner surface of the pores of the carbon material (activated carbon) 110. More specifically, a continuous phase consisting of the cathode active material (sulfur) 120 is filled inside the pores 110a and is also present on the surface of the carbon material (activated carbon) 110, and the solid electrolyte 130 is disposed as a dispersed phase in the continuous phase. As a result, at least a part of the solid electrolyte disposed on the surface of the conductive material (activated carbon) and at least a part of the cathode active material (sulfur) similarly disposed on the surface of the conductive material (activated carbon) are in contact with each other. With such a configuration, it is possible to form a particularly large number of reaction points (three-phase interface), which can effectively contribute to improving the performance of the electric device. Here, whether or not the cathode active material or the solid electrolyte is disposed inside the pores of the conductive material can be confirmed using various conventionally known methods. For example, an image of the cross section of the conductive material contained in the positive electrode material observed with a transmission electron microscope (TEM) can be used to perform elemental mapping of each material using energy dispersive X-ray spectroscopy (EDX), and the arrangement of each material can be confirmed using the obtained elemental map and the count number of the element from each material relative to the count number of all elements as indicators.For example, in the positive electrode material according to the present embodiment, since the solid electrolyte essentially contains phosphorus atoms, if there is no possibility that the phosphorus atoms are derived from other materials, it is possible to obtain the above element map for phosphorus and confirm the arrangement of the solid electrolyte from its distribution. It is also possible to confirm the arrangement of the solid electrolyte from the ratio of the count number of phosphorus to the count number of all elements in EDX. When the arrangement of the solid electrolyte is confirmed using the count number of elements derived only from the solid electrolyte in EDX as an index, if the ratio of the count number of elements derived only from the solid electrolyte to the count number of all elements in EDX is 0.10 or more, it can be determined that the solid electrolyte is arranged inside the pores of the conductive material. The value of the ratio is preferably 0.15 or more, more preferably 0.20 or more, even more preferably 0.26 or more, and particularly preferably 0.35 or more. The larger this value is, the more the solid electrolyte is arranged on the inner surface of the pores of the conductive material. Therefore, when the value of the ratio is within these ranges, the effect of the present invention can be more significantly expressed. There is no particular restriction on the preferred upper limit of the ratio, but a preferred upper limit is, for example, 0.50 or less, and more preferably 0.45 or less.

[0059] According to the cathode material of the present embodiment having the above-mentioned configuration, it is possible to improve the capacity characteristics and cycle durability in an electric device such as an all-solid-state lithium secondary battery using a cathode active material containing sulfur. The mechanism by which such an excellent effect is achieved by adopting the configuration of the present embodiment is not completely clear, but the following mechanism is presumed. That is, in order for the charge / discharge reaction to proceed in the cathode active material containing sulfur, it is necessary for the charge carriers such as electrons and lithium ions to smoothly enter and exit the cathode active material. Here, the present inventors have found through their studies that when the solid electrolyte 130 is present on the surface of the conductive material (carbon material) 110 as relatively large particles as in the cathode material 100' shown in FIG. 3A, the capacity of the lithium secondary battery decreases with the progress of the charge / discharge cycle (i.e., the cycle durability is poor). This is thought to be due to the fact that the cathode active material (sulfur) repeatedly expands and contracts with the progress of the charge / discharge cycle, causing peeling at the interface between the cathode active material (sulfur) and the solid electrolyte, and the three-phase interface consisting of the cathode active material, solid electrolyte, and conductive material necessary for the progress of the battery reaction is reduced.

[0060] In contrast, if the solid electrolyte 130 is present as relatively small particles in a highly dispersed state in the positive electrode active material (sulfur) 120 as in the positive electrode material 100 shown in Fig. 3B, even if the positive electrode active material expands and contracts repeatedly as the charge-discharge cycle proceeds, problems such as peeling at the interface between the positive electrode active material (sulfur) and the solid electrolyte and the resulting reduction in the three-phase interface are unlikely to occur. As a result, even if the charge-discharge cycle proceeds, the charge-discharge reaction can proceed sufficiently, and it is considered that the capacity characteristics and cycle durability are significantly improved.

[0061] An example of a method for producing a positive electrode material according to the present embodiment having the above-mentioned configuration will be described. As described in the Examples section below, first, a solution is prepared by dissolving a solid electrolyte in an organic solvent, and a conductive material is dispersed therein to obtain a dispersion liquid. Next, after removing the solvent, a heat treatment is performed at a temperature of about 150 to 600°C for about 1 to 5 hours. This results in a conductive material in which the pores of the conductive material are impregnated with the solid electrolyte. The present inventors have thus prepared a method for producing a positive electrode material by dissolving a solid electrolyte in an organic solvent. x S y It is presumed that the solid electrolyte is changed to satisfy the peak intensity ratio (R≧0.05) in the Raman spectrum specified in the present application by going through a process in which the solid electrolyte containing the cations (C) and the cations (C) are dissolved in an organic solvent, and then the conductive material is impregnated with the conductive material and the solid electrolyte is precipitated again.

[0062] Next, the obtained conductive material is mixed with a positive electrode active material in a dry state, and then heat-treated for about 1 to 5 hours at a temperature at which the positive electrode active material is in a molten state. As a result, the positive electrode active material melts and penetrates into the pores of the conductive material, and a composite material is obtained in which the positive electrode active material is arranged (filled) together with a solid electrolyte in the pores of the conductive material. The composite material thus obtained may be used as a positive electrode material as it is, but it is preferable to further add a solid electrolyte to the composite material, mix it, and process it in a device such as a ball mill as necessary to obtain a positive electrode material.

[0063] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably within the range of 35 to 99 mass %, and more preferably within the range of 40 to 90 mass %. Note that this content value is calculated based on the mass of only the positive electrode active material excluding the conductive material and the solid electrolyte.

[0064] The positive electrode active material layer may further include a conductive assistant (one that does not hold the positive electrode active material or solid electrolyte inside the pores) and / or a binder. Similarly, the positive electrode active material layer preferably further includes a solid electrolyte in addition to the above-mentioned positive electrode material, and particularly preferably further includes a sulfide solid electrolyte. As for the specific form and preferred form of the solid electrolyte such as the sulfide solid electrolyte, those described in the above-mentioned section on the negative electrode active material layer can be similarly adopted.

[0065] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 27 and the negative electrode current collector plate 25 may be made of the same material or different materials.

[0066] [Positive and negative leads] Although not shown in the figures, the current collectors (11', 11") and the current collecting plates (25, 27) may be electrically connected via positive and negative electrode leads. As the materials for the positive and negative electrode leads, materials used in known lithium secondary batteries may be used. Note that the parts removed from the exterior are preferably covered with a heat-resistant insulating heat-shrink tube or the like to prevent them from coming into contact with peripheral devices or wiring, causing electric leakage and affecting products (e.g., automobile parts, particularly electronic devices, etc.).

[0067] [Battery exterior materials] As the battery exterior material, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum, which can cover the power generating element as shown in Figs. 1 and 2, can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, a laminate film containing aluminum is more preferable as the exterior body because it can easily adjust the group pressure applied to the power generating element from the outside.

[0068] The stacked battery according to the present embodiment has a configuration in which a plurality of unit cell layers are connected in parallel, and thus has high capacity and excellent cycle durability, and is therefore suitable for use as a driving power source for EVs and HEVs.

[0069] While one embodiment of the lithium secondary battery has been described above, the present invention is not limited to the configuration described in the above embodiment, and may be modified as appropriate based on the claims.

[0070] For example, the type of battery to which the lithium secondary battery according to the present invention can be applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically bonded to one surface of a current collector and a negative electrode active material layer electrically bonded to the opposite surface of the current collector.

[0071] In addition, the secondary battery according to the present embodiment does not have to be an all-solid-state type. That is, the solid electrolyte layer may further contain a conventionally known liquid electrolyte (electrolytic solution). There is no particular limit to the amount of liquid electrolyte (electrolytic solution) that can be contained in the solid electrolyte layer, but it is preferable that the amount is such that the shape of the solid electrolyte layer formed by the solid electrolyte is maintained and leakage of the liquid electrolyte (electrolytic solution) does not occur. EXAMPLES

[0072] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to the following examples.

[0073] Example of test cell preparation [Example 1] (Preparation of solid electrolyte-impregnated carbon) In a glove box with an argon atmosphere with a dew point of -68°C or less, 0.500g of sulfide solid electrolyte (Ampcera, Li6PS5Cl) was added to 100mL of ultra-dehydrated ethanol (Fujifilm Wako Pure Chemical Industries, Ltd.), and the solid electrolyte was dissolved in ethanol by stirring thoroughly. 1.00g of carbon (Kansai Thermochemical Industries, Ltd., activated carbon, MSC-30) was added to the obtained solid electrolyte ethanol solution, and the carbon was thoroughly dispersed in the solution by stirring thoroughly. The container containing this carbon dispersion was connected to a vacuum device, and the container was reduced in pressure to 1 Pa or less using an oil rotary pump while stirring the carbon dispersion in the container with a magnetic stirrer. Since ethanol, which is a solvent, volatilizes under reduced pressure, the ethanol was removed over time, and the carbon impregnated with the solid electrolyte remained in the container. After the ethanol was removed under reduced pressure in this way, the solid electrolyte-impregnated carbon was prepared by heating to 180°C under reduced pressure and performing heat treatment for 3 hours.

[0074] (Preparation of sulfur / solid electrolyte / carbon composites by hot impregnation of sulfur) In a glove box with an argon atmosphere at a dew point of -68°C or less, 2.50g of elemental sulfur (manufactured by Aldrich) was added to 0.750g of the solid electrolyte-impregnated carbon prepared above and mixed thoroughly in an agate mortar, and then the mixed powder was placed in a sealed pressure-resistant autoclave and heated at 170°C for 3 hours to melt the sulfur and impregnate the solid electrolyte-impregnated carbon with the sulfur. This produced a sulfur / solid electrolyte / carbon composite material.

[0075] (Preparation of sulfur-containing positive electrode material) In a glove box with an argon atmosphere at a dew point of -68°C or less, 40 g of 5 mm diameter zirconia balls, 0.130 g of the sulfur / solid electrolyte-impregnated carbon prepared above, and 0.070 g of solid electrolyte (Li6PS5Cl, manufactured by Ampcera) were placed in a 45 mL capacity zirconia container, and processed at 370 rpm for 6 hours using a planetary ball mill (Premium line P-7, manufactured by Fritsch) to obtain a powder of sulfur-containing positive electrode material. The composition of the sulfur-containing positive electrode material was sulfur:solid electrolyte:carbon = 50:40:10.

[0076] (Quantitative determination of solid electrolyte components contained inside the pores of conductive materials) The content of the solid electrolyte contained inside the pores of the conductive material (carbon) constituting the powder of the sulfur-containing positive electrode material was quantified by the following method.

[0077] Specifically, to avoid thermal alteration of sulfur and solid electrolyte components, a cryoplasma focused ion beam processing device (Helios G4 PFIB CXe, Thermo Scientific, accelerating voltage: 30 kV) was used to exfoliate powder particles of sulfur-containing cathode material to a thickness of about 100 nm. The exfoliated observation sample was transferred to a TEM device (JEOL, multifunctional analytical transmission electron microscope JEM-F200, accelerating voltage: 200 kV) without exposure to air, and the microstructure was confirmed. At the same time, elemental map data of the part corresponding to the inside of the particle was obtained by an EDX device (energy dispersive X-ray spectrometer, JEOL Dual SDD, accelerating voltage: 200 kV) attached to the TEM (characteristic X-ray measurement energy band of EDX mapping: 0-5 keV). From the obtained elemental map data, the counts of all elements contained in the particle and the counts of elements (phosphorus; P) derived only from the solid electrolyte were obtained. As a result, the ratio of the count number of the element (P) derived only from the solid electrolyte to the count number of all elements was 0.35. From this, it was confirmed that in the sulfur-containing positive electrode material according to this embodiment, the solid electrolyte as well as the sulfur as the positive electrode active material are arranged inside the pores of the conductive material (carbon). Note that an image of the powder particles of the sulfur-containing positive electrode material thus obtained observed by a scanning electron microscope (SEM) is shown in FIG. 4A, and an element map of the phosphorus (P) element in an observation image of the cross section of the conductive material observed by TEM-EDX is shown in FIG. 4B.

[0078] (Microscopic Raman spectroscopy measurement of solid electrolyte components contained in positive electrode materials) A Raman spectrum was obtained by microscopic Raman spectroscopy of the solid electrolyte contained in the powder particles of the sulfur-containing positive electrode material. Here, the Raman analyzer used was an HR manufactured by HORIBA. The measurement conditions were as follows: a 100x objective lens was used, a laser with a wavelength of 532 nm was used as the incident light, and the slit width was 0.1 mm. The measurement range was 0 to 4000 cm. -1The measurement time was 10 seconds, and the number of integrations was 24. The Raman spectrum thus obtained is shown in FIG. 5A. As shown in FIG. 5A, the Raman spectrum of the solid electrolyte contained in the sulfur-containing positive electrode material obtained in this example first shows a peak at 420 cm -1 A peak (Peak A) is shown near the PS4 3- In addition, the Raman spectrum of the solid electrolyte contained in the sulfur-containing positive electrode material obtained in this example shows a peak at 1300 to 1700 cm in addition to the above-mentioned peak A. -1 A peak (peak B) is also shown in the range. Here, when the peak intensity of the peak A is I0 and the peak intensity of the peak with the highest intensity among the peaks B is I1, the peak intensity ratio R (I1 / I0) was calculated to be 0.12.

[0079] (Preparation of test cells (all-solid-state lithium secondary batteries)) The battery was fabricated in a glove box with an argon atmosphere at a dew point of −68° C. or lower.

[0080] A cylindrical convex punch (10 mm diameter) made of SUS was inserted into one side of a cylindrical tube jig made by Macor (tube inner diameter 10 mm, outer diameter 23 mm, height 20 mm), and 80 mg of sulfide solid electrolyte (Li6PS5Cl, made by Ampcera) was inserted from the upper side of the cylindrical tube jig. Then, another cylindrical convex punch made of SUS was inserted to sandwich the solid electrolyte, and a solid electrolyte layer with a diameter of 10 mm and a thickness of about 0.6 mm was formed in the cylindrical tube jig by pressing it for 3 minutes at a pressure of 75 MPa using a hydraulic press. Next, the cylindrical convex punch inserted from the upper side was once removed, and 7.5 mg of the sulfur-containing positive electrode mixture prepared above was placed on one side of the solid electrolyte layer in the cylindrical tube, and a cylindrical convex punch (which also serves as a positive electrode current collector) was inserted from the upper side again and pressed for 3 minutes at a pressure of 300 MPa to form a positive electrode active material layer with a diameter of 10 mm and a thickness of about 0.06 mm on one side of the solid electrolyte layer. Next, the lower cylindrical convex punch (which also served as the negative electrode current collector) was removed, and a lithium foil (manufactured by Nilaco Corporation, thickness 0.20 mm) punched to a diameter of 8 mm and an indium foil (manufactured by Nilaco Corporation, thickness 0.30 mm) punched to a diameter of 9 mm were stacked as the negative electrode. The cylindrical tube jig was inserted from the bottom so that the indium foil was positioned on the solid electrolyte layer side, and the cylindrical convex punch was inserted again and pressed at a pressure of 75 MPa for 3 minutes to form a lithium-indium negative electrode.

[0081] In this manner, a test cell (all-solid-state lithium secondary battery) was produced in which a negative electrode current collector (punch), a lithium-indium negative electrode, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector (punch) were stacked in this order.

[0082] [Example 2] An all-solid-state lithium secondary battery was produced in the same manner as in Example 1 described above, except that in the preparation of the solid electrolyte-impregnated carbon, the conditions for removing ethanol under reduced pressure were changed to heating on a hot plate at 50° C. for 3 hours under atmospheric pressure in a glove box with an argon atmosphere having a dew point of −68° C. or lower.

[0083] In this embodiment, it was confirmed that the solid electrolyte was arranged inside the pores of the conductive material (carbon) together with sulfur, which is the positive electrode active material. In addition, the Raman spectrum was obtained by performing microscopic Raman spectroscopy measurement in the same manner as above for the sulfur-containing positive electrode material prepared in this embodiment. The peak intensity ratio R (I1 / I0) was calculated in the same manner as above and was 0.10.

[0084] [Example 3] An all-solid-state lithium secondary battery was produced in the same manner as in Example 1 described above, except that in the preparation of the solid electrolyte-impregnated carbon, the conditions of the reduced pressure heat treatment after the reduced pressure removal of ethanol were changed to 250° C. for 3 hours.

[0085] In this embodiment, it was confirmed that the solid electrolyte was arranged inside the pores of the conductive material (carbon) together with sulfur, which is the positive electrode active material. In addition, the Raman spectrum was obtained by performing microscopic Raman spectroscopy measurement in the same manner as above for the sulfur-containing positive electrode material prepared in this embodiment. The peak intensity ratio R (I1 / I0) was calculated in the same manner as above and was 0.07.

[0086] [Example 4] An all-solid-state lithium secondary battery was produced in the same manner as in Example 1 described above, except that in the preparation of the solid electrolyte-impregnated carbon, the conditions for removing ethanol under reduced pressure were changed to heating on a hot plate at 50°C for 3 hours under atmospheric pressure in a glove box with an argon atmosphere having a dew point of -68°C or lower, and the conditions for the reduced pressure heat treatment were changed to 250°C for 3 hours.

[0087] In this embodiment, it was confirmed that the solid electrolyte was arranged inside the pores of the conductive material (carbon) together with sulfur, which is the positive electrode active material. In addition, the sulfur-containing positive electrode material prepared in this embodiment was subjected to microscopic Raman spectroscopy measurement in the same manner as above to obtain a Raman spectrum. The peak intensity ratio R (I1 / I0) was calculated in the same manner as above and was found to be 0.05.

[0088] [Comparative Example 1] Preparation of solid electrolyte-impregnated carbon and thermal impregnation with sulfur were not performed. Instead, 40 g of zirconia balls with a diameter of 5 mm, 0.100 g of sulfur, 0.080 g of solid electrolyte, and 0.020 g of carbon were placed in a 45 mL zirconia container in a glove box in an argon atmosphere with a dew point of -68°C or less, and processed for 6 hours at 370 rpm with a planetary ball mill. The sulfur / solid electrolyte / carbon mixed powder was then placed in a sealed pressure-resistant autoclave container and heated at 170°C for 3 hours to obtain a powder of sulfur-containing positive electrode material. Except for these, an all-solid-state lithium secondary battery was produced by the same method as in Example 1 described above.

[0089] The sulfur-containing positive electrode material prepared in this comparative example was subjected to microscopic Raman spectroscopy in the same manner as described above to obtain a Raman spectrum. The Raman spectrum thus obtained is shown in FIG. 5B. As shown in FIG. 5B, the Raman spectrum of the solid electrolyte contained in the sulfur-containing positive electrode material obtained in this comparative example first shows a peak at 420 cm -1 A peak (Peak A) is shown near the PS4 3- On the other hand, the Raman spectrum of the solid electrolyte contained in the sulfur-containing positive electrode material obtained in this comparative example is different from the Raman spectrum of Example 1 shown in FIG. -1 The peak (peak B) in this range is extremely small. Here, the peak intensity ratio R (I1 / I0) was calculated by taking the peak intensity of the peak A as I0 and the peak intensity of the peak with the highest intensity among the peaks B as I1, and was found to be 0.03.

[0090] [Comparative Example 2] No preparation of solid electrolyte-impregnated carbon was performed. In a glove box in an argon atmosphere with a dew point of -68°C or less, 40g of zirconia balls with a diameter of 5mm, 0.080g of solid electrolyte, and 0.020g of carbon were placed in a zirconia container with a capacity of 45mL, and processed for 6 hours at 370 rpm with a planetary ball mill. Thereafter, sulfur was added to the obtained solid electrolyte / carbon mixed powder in a mass ratio of 1:1, and the mixture was thoroughly mixed in an agate mortar, and then placed in a sealed pressure-resistant autoclave container and heated at 170°C for 3 hours to obtain a powder of a sulfur-containing positive electrode material. Except for these, an all-solid-state lithium secondary battery was produced by the same method as in Example 1 described above.

[0091] The sulfur-containing positive electrode material prepared in this comparative example was subjected to microscopic Raman spectroscopy to obtain a Raman spectrum in the same manner as described above. The peak intensity ratio R(I1 / I0) was calculated in the same manner as described above to be 0.01.

[0092] [Comparative Example 3] Without preparing solid electrolyte-impregnated carbon, 2.50 g of sulfur was added to 0.500 g of carbon and mixed thoroughly in an agate mortar, and the mixed powder was placed in a sealed pressure-resistant autoclave and heated at 170°C for 3 hours to melt the sulfur and impregnate the carbon with sulfur. Thus, sulfur-impregnated carbon was obtained.

[0093] Next, 0.120 g of sulfur-impregnated carbon, 0.080 g of sulfide solid electrolyte, and 40 g of zirconia balls with a diameter of 5 mm were placed in a 45 mL zirconia container and treated with a planetary ball mill at 370 rpm for 6 hours to obtain a powder of a sulfur-containing positive electrode material.

[0094] Other than these, an all-solid-state lithium secondary battery was produced in the same manner as in Example 1 described above.

[0095] The sulfur-containing positive electrode material prepared in this comparative example was subjected to microscopic Raman spectroscopy to obtain a Raman spectrum in the same manner as described above. The peak intensity ratio R (I1 / I0) was calculated in the same manner as described above and was found to be less than 0.01.

[0096] [Comparative Example 4] Preparation of solid electrolyte-impregnated carbon and thermal impregnation with sulfur were not performed, and 40 g of 5 mm diameter zirconia balls, 0.100 g of sulfur, 0.080 g of solid electrolyte, and 0.020 g of carbon were placed in a 45 mL capacity zirconia container in a glove box in an argon atmosphere with a dew point of -68°C or less, and treated with a planetary ball mill at 370 rpm for 6 hours. After that, an all-solid-state lithium secondary battery was produced in the same manner as in Example 1 described above, except that the sulfur / solid electrolyte / carbon mixed powder was placed in a sealed pressure-resistant autoclave container and heated at 170°C for 3 hours.

[0097] The sulfur-containing positive electrode material prepared in this comparative example was subjected to microscopic Raman spectroscopy to obtain a Raman spectrum in the same manner as described above. The peak intensity ratio R (I1 / I0) was calculated in the same manner as described above and was found to be less than 0.01.

[0098] <Test cell evaluation example> The test cells prepared in the above examples and comparative examples were evaluated for capacity characteristics and cycle durability by the following methods. All of the following measurements were performed using a charge-discharge tester (HJ-SD8, manufactured by Hokuto Denko Corporation) in a constant temperature bath set at 25°C.

[0099] (Evaluation of capacitance characteristics) The test cell was placed in the thermostatic chamber, and after the cell temperature had stabilized, the cell was conditioned with a current of 0.2 mA / cm. 2 The cell was discharged to a cell voltage of 0.5 V at a current density of 0.01 mA / cm2, followed by a constant-current constant-voltage charge to 2.5 V at the same current density with a cutoff current of 0.01 mA / cm2. 2The charging and discharging capacity was calculated from the charge and discharge capacity obtained after repeating this conditioning charge and discharge cycle 10 times and the mass of the positive electrode active material contained in the positive electrode. The results are shown in Table 1 below.

[0100] (Evaluation of cycle durability) One cycle consisted of a process of fully charging the battery at a constant current and constant voltage of 0.05C-2.5V with a cutoff current of 0.01C, followed by discharging at 0.05C with a cutoff voltage of 0.5V. The discharge capacity retention rate at the 50th cycle [%] was calculated as the percentage of the discharge capacity at the 50th cycle to the discharge capacity at the first cycle. The results are shown in Table 1 below.

[0101] [Table 1]

[0102] The results shown in Table 1 demonstrate that, according to the present invention, improvements in capacity characteristics and cycle durability can be achieved in an all-solid-state lithium secondary battery using a positive electrode active material containing sulfur. [Explanation of symbols]

[0103] 10a Stacked battery, 11' negative electrode current collector, 11” positive electrode current collector, 13 negative electrode active material layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21 Power generation elements, 25 negative current collector plate, 27 Positive current collector, 29 Laminating film, 100,100' Positive electrode material, 110 Carbon materials (activated carbon), 110a pores, 120 Cathode active material (sulfur), 130 Solid electrolyte.

Claims

1. A conductive material and phosphorus sulfide (P x S y ) and a positive electrode active material containing sulfur, at least a portion of the solid electrolyte and at least a portion of the positive electrode active material are disposed on a surface of the conductive material so as to be in contact with each other; The solid electrolyte contained in the positive electrode material was measured by microscopic Raman spectroscopy using a laser with a wavelength of 532 nm, and the Raman spectrum was found to have a peak at 420 cm -1 Nearby PS 4 3- and a peak A derived from 1300 to 1700 cm -1 Peak B is shown in the range of The peak intensity of the peak A is I 0 The peak intensity of the peak B with the highest peak intensity is I 1 When the peak intensity ratio R (I 1 / I 0 ) satisfies R≧0.

05.

2. The positive electrode material for an electric device according to claim 1 , wherein R satisfies R≧0.

10.

3. The positive electrode material for an electric device according to claim 2 , wherein R satisfies R≧0.

12.

4. The positive electrode material for an electric device according to any one of claims 1 to 3, wherein the conductive material is a conductive material having pores.

5. 5. The positive electrode material for an electric device according to claim 4, wherein a continuous phase made of the positive electrode active material fills the inside of the pores, and the solid electrolyte is disposed as a dispersed phase in the continuous phase.

6. 6. The positive electrode material for an electric device according to claim 4, wherein the conductive material has a pore volume of 1.0 mL / g or more.

7. The positive electrode material for an electric device according to any one of claims 4 to 6, wherein the conductive material has an average pore size of 50 nm or less.

8. 8. The positive electrode material for an electric device according to claim 1, wherein in a TEM-EDX observation image of a cross section of the conductive material contained in the positive electrode material, a ratio of the count number of elements derived only from the solid electrolyte to the count number of all elements is 0.10 or more.

9. The positive electrode material for an electric device according to any one of claims 1 to 8, wherein the conductive material is a carbon material.

10. 10. The positive electrode material for an electric device according to claim 1, wherein the solid electrolyte contains an alkali metal.

11. 11. The positive electrode material for an electrical device according to claim 10, wherein the alkali metal is lithium.

12. The positive electrode material for an electric device according to any one of claims 1 to 11, wherein the positive electrode active material is elemental sulfur or lithium sulfide.

13. An all-solid-state lithium secondary battery comprising the positive electrode material for an electric device according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • All-solid lithium battery positive electrode, and secondary battery including the same

    JP2016127005A

  • Composite material of alkali metal sulfide and conducting agent

    WO2012102037A1

  • Composite material

    WO2014162693A1